Environmental Characteristics Associated With Residential Burglaries Of Student Apartment Complexes - Robinson, Matthew B. (Environment and behavior, 1997)
This study identified environmental characteristics associated with residential burglaries of apartment complexes predominantly occupied by students, located near two major universities and a community college in Tallahassee, Florida. Through observation and measurement of environmental characteristics, results showed that accessibility played little role in differentiating burglarized and nonburglarized apartment units. Yet, burglarized units were disproportionately likely to be located on the corner of the building and on the first floor. Results also showed that apartment units with reported burglaries in 1993 were less surveillable than apartment units with no reported burglaries--i.e., burglarized units were more obstructed by foliage or structure. Finally, through surveying student apartment residents, results suggested that burglaries largely occurred at times when students reported being away from their apartments for purposes of attending classes, engaging in recreational activities, or shopping. The results add additional support for the well-established link between environmental characteristics and residential burglary